PERAN LAYANAN KONSELING INDIVIDU DENGAN PENDEKATAN BEHAVIORISTIK TEKNIK OPERANT CONDITIONING DALAM MENGURANGI PERILAKU HIPERAKTIF–IMPULSIF (PREDOMINANTLY HIPERAKTIF–IMPLUSIF TYPE) PADA PESERTA DIDIK KELAS IX DI SMP MUHAMMADIYAH 2 SURAKARTA TAHUN 2025: Penelitian Tindakan Bimbingan dan Konseling - Aminah, Siti; Adi Putro, Eko; Jawandi, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students are expected to fully engage in their subjects and be present in the learning process. It is crucial for students to maximize their concentration abilities to effectively absorb the learning material. Hyperactive-Impulsive behavior refers to an individual's difficulty in controlling their urge to move or speak very actively. If not addressed promptly, students may receive negative evaluations from their surroundings and be perceived as disruptive to the teaching and learning process in the classroom. The purpose of this study is to determine the role of individual counseling services using a behavioral approach with Operant Conditioning techniques in reducing hyperactive-impulsive behavior (predominantly Hyperactive-Impulsive type) among ninth-grade students at Muhammadiyah 2 Junior High School in Surakarta for the 2025 academic year. This research is a Guidance and Counseling Action Research (PTBK) conducted in three cycles, each consisting of four stages: planning, action, observation, and reflection. The data analysis technique used is triangulation, which involves comparing behavioral changes at the initial condition, Cycle I, Cycle II, and Cycle III. Data collection techniques include interviews, observations, and documentation. Based on the results of Cycle I, a behavior reduction of 45.5% was achieved, with a decrease in behavior intensity of 7 out of 23 indicator points; Cycle II showed a behavior reduction of 24%, with a decrease in behavior intensity of 3 out of 23 indicator points; and Cycle III resulted in a behavior reduction of 0%, with no change in behavior intensity (0 out of 23 indicator points). From this research, it can be concluded that the role of Individual Counseling Services using a Behavioral Approach with Operant Conditioning techniques can reduce hyperactive-impulsive behavior (Predominantly Hyperactive-Impulsive Type) among ninth-grade students.